Local Plant Treasures and Functions of Pantun Batobo - Alvi Puspita; Raja Syamsidar; TM. Sum (Hasanuddin University, 2022)
Pantun Batobo is a type of pantun in the Kampar area, Riau Province. This pantun is hummed when doing batobo activities. Batobo is a mutual cooperation activity in working on the fields, starting from the process of planting to harvesting. This study examines the pantun batobo by focusing on two aspects, namely the treasures of local plants found in the pantun and the function of the pantun. Data collection methods used are interview methods and recording techniques. The data analysis method uses descriptive analysis method. The theory used is Alan Dundes' Function Theory and Ecocritical Theory. The results obtained from this study are that from an eco-critic perspective, the batobo pantun is rich in knowledge of local plant treasures stored in the rhyme sampirans. This shows the close kinship between the people who own the pantun and the nature around it. In terms of function, this pantun has a function as a fun escape from reality and turns boring work into a game. The pantun batobo is not only a pantun muda-mudi filled with feelings, but it contains the perspective of the people who own the pantun about macrocosm and microcosm.